Telmisartan mitigates lipopolysaccharide (LPS)-induced production of mucin 5AC (MUC5AC) through increasing suppressor of cytokine signaling 1 (SOCS1). Issue 1 (1st January 2021) - Chen, Ling; Xu, Jiajia; Deng, Meiyu; Liang, Yanling; Ma, Jinfu; Zhang, Linghui; Wang, Yijie; Zhang, Jinping
ABSTRACT: Acute lung injury (ALI) is a serious clinical pulmonary disease. The pathogenesis of ALI is related to the excessive release of inflammatory factors and upregulation of mucin 5AC (MUC5AC). Telmisartan is a novel antihypertension agent that exerts promising anti-inflammatory effects. The purpose of this study is to investigate whether Telmisartan has a protective role in lipopolysaccharide (LPS)-induced MUC5AC expression and to explore the underlying mechanism in human bronchial epithelial cells. Firstly, the decreased cell viability, elevated release of lactate dehydrogenase (LDH), and excessively released inflammatory factors tumor necrosis factor-α (TNF-α), interleukin- 6 (IL-6), and transforming growth factor-β (TGF)-β in bronchial BEAS-2B epithelial cells induced by stimulation with LPS were significantly reversed by the introduction of Telmisartan. Secondly, the upregulated MUC5AC and downregulated suppressor of cytokine signaling 1 (SOCS1) caused by stimulation with LPS were dramatically reversed by Telmisartan. Notably, treatment with Telmisartan attenuated LPS-induced activation of nuclear factor κ-B (NF-κB). Lastly, silencing of SOCS1 abolished the protective effects of Telmisartan against LPS-induced production of MUC5AC and the activation of NF-κB. Based on these findings, we conclude that Telmisartan displayed a protective effect against LPS by improving mitochondrial function, mitigating inflammatory response, and reducing the production of mucin 5AC by regulating the SOCS1/NF-κB axis in human bronchial epithelial cells. Graphical abstract: uf0001